Developing sustainable, green and inclusive agricultural value chains in the Caribbean and the Pacific Islands; based on case studies by Robert A. Best (Caribbean) and Koko Siga Pacific (Pacific Islands) - Westlake, Michael J. (CTA & FAO BrusselsBE, 2014)
Aims to draw comparisons between value chains in these tow regions that have much in common. Reviews a wide range of factors affecting commercial value chain development in the two regions, with emphasis being placed on how the chains studied have maximised the inclusion of smallholders and on identifying ways in which they have been able to address sustainability concerns.